TEOLOGI MAUT VS TEOLOGI PEMBEBASAN ASGHAR ALI ENGINEER - Putra, Rido; Amril, Amril; Rido Putra (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This article describes the actions of resistance carried out by groups of adherents of